Analysis of Farmer Behavior in Turmeric Farming: Moscardi and De Janvry Approach in Driyorejo District: Analisis Perilaku Petani dalam Usahatani Kunyit: Pendekatan Moscardi and De Janvry di Kecamatan Driyorejo - Riadhu Sholikhah; Mirza Andrian Syah; Ida Syamsu Roidah (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabaya, 2026)
Fluctuations in turmeric production in Driyorejo Regency during 2020–2024 indicate uncertainty in harvest yields and income, potentially influencing farmers' behavior in making agricultural decisions. This study aims to analyze farmers' behavior towards the risks of turmeric cultivation in Driyorejo Regency, Gresik Regency, using the Moscardi and De Janvry approach. This study was conducted in February 2026, involving 50 turmeric farmers selected using a snowball sampling technique. The analysis was conducted using the risk aversion coefficient [K(s)] parameter, with seed elasticity as the most dominant input influencing turmeric productivity. The results showed that 32 farmers (64%) were classified as risk neutral and 18 farmers (36%) were classified as risk takers, while no farmers were found to be risk averse. These findings indicate that turmeric farmers tend to be neutral to risk averse because turmeric cultivation in an intercropping system is considered capable of providing additional income, spreading risks between commodities, and increasing land management efficiency. Theoretically, the results of this study reinforce the safety-first principle that farmers tend to implement to maintain agricultural sustainability at a tolerable level of risk.